2022
DOI: 10.1002/smll.202203723
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional Nanodot Arrays in Living Cells Uncover Synergistic Co‐Condensation of Wnt Signalodroplets

Abstract: Qualitative and quantitative analysis of transient signaling platforms in the plasma membrane has remained a key experimental challenge. Here, biofunctional nanodot arrays (bNDAs) are developed to spatially control dimerization and clustering of cell surface receptors at the nanoscale. High-contrast bNDAs with spot diameters of 300 nm are obtained by capillary nanostamping of bovine serum albumin bioconjugates, which are subsequently biofunctionalized by reaction with tandem anti-green fluorescence protein (GF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
2
3
0
Order By: Relevance
“…By contrast, co-clustering of Lrp6/Fzd8 into distinct signalosomes took place one order-of-magnitude slower timescale (~20 min), exhibiting distinct features of a nucleation-growth process. These characteristics are well in line with recent models suggesting receptor dimerization triggering the formation of canonical Wnt signalosomes by co-condensation with the scaffold proteins Axin and Dvl [35,37]. Strikingly, Ror2, the co-receptor for noncanonical Wnt signaling, which is not recognized by NGS, was found transiently trapped in NGS-induced canonical signalosomes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…By contrast, co-clustering of Lrp6/Fzd8 into distinct signalosomes took place one order-of-magnitude slower timescale (~20 min), exhibiting distinct features of a nucleation-growth process. These characteristics are well in line with recent models suggesting receptor dimerization triggering the formation of canonical Wnt signalosomes by co-condensation with the scaffold proteins Axin and Dvl [35,37]. Strikingly, Ror2, the co-receptor for noncanonical Wnt signaling, which is not recognized by NGS, was found transiently trapped in NGS-induced canonical signalosomes.…”
Section: Discussionsupporting
confidence: 89%
“…Within these signalosomes, however, Lrp6 clearly showed mobility ( Fig. S5I-L , Movie S6 ), in line with condensate-like properties of these clusters, which we and others have recently proposed [37, 48, 49]. We further quantified Lrp6 confinement by pair correlation analysis [43, 47] ( Fig.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…[56] For example, Wnt "signalodroplets" formed by LLPS that bind to the plasma membrane can amplify Wnt signaling. [57] Transmembrane proteins are not the only ones that can nucleate and localize condensates; nonspecific interactions between lipids and disordered proteins could also induce phase separation. Recently, Chatterjee et al showed that the presence of SUVs containing anionic DOPS and DOPG lipids could induce the formation of clusters of FUS low complexity (LC) domain and lipids at a 30-fold lower concentration than that needed for FUS LC phase separation in the absence of lipids, caused by FUS LC binding to SUVs and adopting a more ordered conformation (Figure 4e).…”
Section: Controlling Coacervate Formation and Localizationmentioning
confidence: 99%
“…[ 56 ] For example, Wnt “signalodroplets” formed by LLPS that bind to the plasma membrane can amplify Wnt signaling. [ 57 ]…”
Section: Controlling Coacervate Formation and Localizationmentioning
confidence: 99%